Cigarette smoke compromises macrophage innate sensing in response to pneumococcal infection - Wei-Chih Liao; Chia-Huei Chou; Mao-Wang Ho; Jo-Tsen Chen; Shu-Ling Chou; Yu-Tsen Huang; Ngoc-Niem Bui; Hui-Yu Wu; Chi-Fan Lee; Wei-Chien Huang; Chih-Ho Lai (Journal of Microbiology, Immunology and Infection)
Background: Cigarette smoking remains a leading cause of mortality worldwide. Streptococcus pneumoniae, also known as pneumococcus, is one of the most common pathogens that colonizes the human respiratory tract, causing life-threatening infections. Several studies have reported that cigarette smoke (CS) exposure promotes pneumococcal infectivity; however, the underlying mechanisms remain to be illustrated. Methods: In this study, we prepared cigarette smoke extract (CSE) from tobacco containing nicotine (0.8 mg/cigarette) and tar (10 mg/cigarette) to investigate the effects of CSE on innate immune response using murine macrophage models. Results: The results from the cytokine array showed that the production of C-C Motif Chemokine Ligand 2 (CCL2), CCL4, CCL3, C-X-C Motif Chemokine Ligand 2 (CXCL2), and CXCL-10, in pneumococcus-infected cells was reduced upon 5 % CSE treatment. Our results further demonstrated that 5 % CSE exposure, followed by pneumococcal challenge, significantly decreased CCL2 and type I interferon (IFN) production in macrophages by inhibiting nuclear factor (NF)-κB and IFN regulatory factor 3 (IRF3) signaling pathways. Moreover, CSE disrupts macrophage polarization and impedes innate immune signaling to suppress pneumococcal phagocytosis by macrophages. Conclusion: Our results provide evidence that CS manipulates the signaling molecules to subvert macrophage functions, thereby hindering the innate response against pneumococcal infection.